Selection or influence? Institutional investors and acquisition targets - Lily Qiu; Hong Wan (Brown University, Department of Economics, 2006)
This paper shows that the positive correlation between the presence of institutional investors and a firm's likelihood of being acquired is due to ownership endogeneity, i.e., due to the fact that institutions are better informed investors. After controlling for this ownership endogeneity, the presence of institutional investors reduces the probability of being acquired. There is also evidence that mutual funds or funds with high turnover rates are more likely to benefit from selective disclosure prior to Regulation Fair Disclosure. The presence of public pension funds increases the announcement premium that targets receive.
Keywords: 330; Institutioneller Anleger; Übernahme; Publizitätspflicht; USA